2004
DOI: 10.1385/bter:99:1-3:049
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Deficiency and Growth: Current Concepts in Relationship to Two Important Points: Intellectual and Sexual Development

Abstract: Zinc deficiency remains a serious health problem worldwide affecting developed as well as developing countries. Despite the evidence proving that zinc deprivation during the periods of rapid growth negatively affects the cognitive brain as well as sexual development, there are few complete studies carried out in children. The present article proposes a revision of the evidence gathered until now on the relationship existing between zinc deficiency and intellectual and sexual development during the stages of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 53 publications
0
7
0
2
Order By: Relevance
“…Studies of humans suggest a correlation between serum zinc concentrations, birthweight, and pregnancy outcome (Neggers et al, 1990;Tamura et al, 2000;Hambidge and Krebs, 2003); dietary zinc supplementation has been reported to exert therapeutic and preventative effects on low birthweight and childhood disease in several developing countries (Black, 1998b;Allen, 1998;Caulfield et al, 1998). It is also interesting to note that zinc deficiency in humans has been correlated with abnormal fetal development (Bloxam and Bax, 1996), diabetes and schizophrenia (Andrews, 1992), decreased cognitive behavior and intellectual development (Black, 1998a;Salgueiro et al, 2004), and increased mortality and disease (Black, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of humans suggest a correlation between serum zinc concentrations, birthweight, and pregnancy outcome (Neggers et al, 1990;Tamura et al, 2000;Hambidge and Krebs, 2003); dietary zinc supplementation has been reported to exert therapeutic and preventative effects on low birthweight and childhood disease in several developing countries (Black, 1998b;Allen, 1998;Caulfield et al, 1998). It is also interesting to note that zinc deficiency in humans has been correlated with abnormal fetal development (Bloxam and Bax, 1996), diabetes and schizophrenia (Andrews, 1992), decreased cognitive behavior and intellectual development (Black, 1998a;Salgueiro et al, 2004), and increased mortality and disease (Black, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of Zn on various components of the immune system and its direct gastrointestinal effects has led to the use of Zn in the prevention and treatment of diarrhea in children [14,16]. Other consequences of Zn deficiency are anorexia, growth retardation, disorders of neurodevelopment, hypogonadism and mental lethargy [14,15,17,18]. Most of these disorders are also seen in children with CRF, and it is possible that Zn deficiency may aggravate them.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary zinc deficiency correlates with low birth weight and poor pregnancy outcome in humans [2][4], and has been associated with abnormal fetal development [5], diabetes and schizophrenia [6], decreased cognitive behavior and intellectual development [7], [8], and impaired host defense [9]. Zinc deficiency increases mortality and disease [10].…”
Section: Introductionmentioning
confidence: 99%